THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON THE CREATIVE THINKING ABILITY OF GRADE V STUDENTS ON THE VOLUME OF BUILDING SPACE AT SD NEGERI 10 BANDA ACEH - Marfirah, Ayu; Fauzi, Fauzi; Ahadin, Ahadin (Universitas Syiah Kuala, 2025)
Mathematics has a central role in solving various problems in everyday life. Despite this, many students find mathematics difficult and intimidating. This research aims to overcome the problem of lack of creative thinking abilities in class V students at SDN 10 Banda Aceh by applying the Problem Based Learning (PBL) learning model. The research method used was an experiment with a True Experimental Pretest-Posttest Control Group Design. The population of this study was all fifth grade students at SDN 10 Banda Aceh (40 people), and samples were taken using purposive sampling technique, with 20 students as the experimental group and 20 students as the control group. The PBL model was applied to the experimental group, while the control group did not use the Problem Based Learning model. Data was collected through pretest and posttest in both groups. Data analysis uses statistical tests with a significance value (2-tailed) of 0.0150.05. The results of the research show that there is an influence of the PBL model on problem solving abilities in equivalent fraction material in class V at SDN 10 Banda Aceh. Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The PBL model succeeded in increasing students' creative thinking abilities significantly. This research makes a positive contribution to the development of mathematics learning methods that can increase student engagement and their creative thinking abilities. The practical implication of this research is the need to apply the PBL model in improving the quality of mathematics learning in elementary schools.